STRATEGI MANAJEMEN PENDIDIKAN BERBASIS BUDAYA SEKOLAH DALAM MEMPERKUAT DELAPAN DIMENSI PROFIL LULUSAN DI SMK NEGERI 1 KARANGDADAP - Alisa Rizca Puspita; Beni Habibi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the implementation of a school culture-based educational management strategy to strengthen the eight dimensions of the graduate profile at SMK Negeri 1 Karangdadap. The study was motivated by the need for vocational schools to produce graduates who possess not only technical competencies but also strong character, critical thinking, creativity, collaboration, communication skills, independence, and global competitiveness. The objective of this research was to analyze the educational management strategies implemented through school culture, identify supporting and inhibiting factors, and describe their contribution to strengthening the graduate profile. A qualitative approach with a case study design was employed. Data were collected through observations, in-depth interviews, documentation, and field notes involving the principal, teachers, educational staff, and students. Data validity was ensured through source and technique triangulation, while data were analyzed using the interactive model of data reduction, data display, and conclusion drawing. The findings reveal that school culture-based educational management has been implemented systematically through leadership, character habituation programs, religious activities, collaborative learning, extracurricular programs, and partnerships with industry. These strategies have contributed positively to strengthening the eight dimensions of the graduate profile by fostering students' character, discipline, collaboration, creativity, communication, and work readiness. The implementation is supported by strong leadership commitment, teacher involvement, and stakeholder collaboration, although challenges remain in terms of infrastructure, student diversity, and parental participation. The study concludes that integrating school culture into educational management is an effective strategy for improving the quality of vocational education and preparing graduates with competencies and character that meet the demands of the twenty-first century.